Food waste and generation management of selected barangays in Quezon City a case study - Caballero, Niña Marie; Bullecer, Ernani R.; Malabad, Cristina G.; Cochon, Kim L.; Mira, Nona Rachel C.; Ignacio, Ma. Socorro E. (Manila College of Public Health, University of the Philippines Manila, 2019)
There are limited studies on the food waste generation and its management in urban cities in Philippines since it is assumed that as a developing country most of its food waste, especially that can be avoided, mostly occurred at the upper stages of food supply chain. In line with this, this paper aimed to measure the proportion of household with avoidable food waste and the average generation of avoidable food waste in selected barangay/s in Quezon City as well as its management at the barangay level.

This study was a case study of one city using a mixed method specifically concurrent triangulation design. This also included a survey of household avoidable food waste using household inventory list and key informant interviews of barangay officials and staff involved on food waste management. Three barangays in Quezon City were pre-selected as study areas. A total of 228 household respondents for household quantification of food waste and 4 key informant interviews of barangay officials/staff were used to analyze its key population mean were employed. Content analysis was utilized to analyze the key informant interviews.

The proportion of households with avoidable food waste was 0.7 with 95% CI of 0.64–0.76 while the average household avoidable food waste was 127.17 grams with SD of 137.0 grams and 95% CI of 100.50–154.50. The most common strategy present at barangay level was the collection and segregation of food waste as well as informational campaign. Among the three areas, only one had on-going program on food waste which was composting. The most prominent challenge of the officials in terms of reducing food waste was the behavior of their residents since most of them lack the commitment and participation on the implementation of programs. None of the three barangays has achieved successes on reducing food waste.

The findings of this study conclude that food waste is a growing concern in the three studied areas since many households waste considerable amount of avoidable food waste. The challenges encountered by the barangay officials should be given attention to fully manage food waste occurring in their area. Their concerns are very valuable in formulating policies regarding food waste management. Importantly, the results from this study could be used as baseline data for future research on food waste specifically in Philippines.
Includes references and appendices.
Thesis
Keywords: Food waste -- Management -- Case studies. -- Philippines -- Quezon City; Refuse and refuse disposal -- Management -- Case studies. -- Philippines -- Quezon City; Municipal solid waste -- Management -- Case studies. -- Philippines -- Quezon City; Waste minimization -- Case studies. -- Philippines -- Quezon City; Quezon City (Philippines) -- Environmental conditions -- Case studies